2022
DOI: 10.1177/20552076221129066
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a tailored and virtually supported home exercise program for people with multiple myeloma using a novel eHealth application

Abstract: Introduction eHealth exercise interventions have the unique ability to leverage the benefits of in-person programming (tailoring and supervision) with the benefits of home programming (flexibility). There may be a role for eHealth-delivered exercise for people with multiple myeloma (MM), as exercise tailoring and supervision are critical for successful outcomes due to the significant impacts/risks of myeloma-related side effects. The purpose of this study was to determine the safety, feasibility, and prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The present study is an acceptability-focused sub-study of MY PROGRESS, a larger multi-method feasibility study. A detailed overview of the exercise intervention, the HEAL-Me app, and quantitative feasibility results from MY PROGRESS are published elsewhere [ 13 ]. This qualitative study represents phase two of the overall study and complements phase one’s quantitative feasibility measures by eliciting participant feedback, thus developing a deeper understanding of program acceptability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is an acceptability-focused sub-study of MY PROGRESS, a larger multi-method feasibility study. A detailed overview of the exercise intervention, the HEAL-Me app, and quantitative feasibility results from MY PROGRESS are published elsewhere [ 13 ]. This qualitative study represents phase two of the overall study and complements phase one’s quantitative feasibility measures by eliciting participant feedback, thus developing a deeper understanding of program acceptability.…”
Section: Methodsmentioning
confidence: 99%
“…The Myeloma Progressive Resistance and Aerobic Exercise Study (MY PROGRESS) was a 12-week virtually supported home exercise program delivered using a novel eHealth exercise application, the HEAL-Me app [ 13 ]. It sought to balance the benefits of center-based programming (supervision) with the benefits of home programming (flexibility) using a combination of app-based supervised group exercise sessions and independent exercise sessions.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile apps promoting physical activity can improve cancer-related fatigue, sedentary lifestyle, and psychosocial outcomes [121], also through personalized home exercise programs [122,123]. As cancer mortality declines, digital interventions delivering physical exercise interventions for cancer survivors are of equal importance [124].…”
Section: Cancermentioning
confidence: 99%
“…34 Often these programs allow users to access predetermined exercise routines, track dietary intake and exercise sessions and connect with other users. Recent evidence has shown that e-Health exercise interventions are safe, feasible and enjoyable for patients with chronic disease 35,36 and have clinical use in improving various health markers. [37][38][39] Mobile health (mHealth) involves the use of mobile devices to provide exercise care.…”
Section: Ask and (Re)assess: Measuring And Monitoringmentioning
confidence: 99%